1998
DOI: 10.1046/j.1365-2605.1998.00102.x
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary‐dependent expression of the testicular angiotensin II receptor and its subtypes in rats

Abstract: Angiotensin II (AT2) has been implicated in the growth and/or differentiation of its target tissues. In the present study, testicular AT2 receptor and its subtypes in hypophysectomized rats were examined using quantitative in vitro autoradiography and Northern blot analysis in an attempt to determine possible involvement of pituitary hormones in their expression. Prepubescent (3 weeks of age) male Sprague-Dawley rats underwent hypophysectomy or sham operation. From 10 days thereafter, they were treated with ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Aguilera et al (7) reported also a decrease in ANG II binding during development and that in immature rat a high proportion of ANG II receptors in the testes are located in nondifferentiated mesenchymal cells of the interstitium. Hypophysectomy led to a marked increase in AT 1 and AT 2 receptor concentration of rat testis with predominant occurrence of AT 1 receptors measured by in vitro autoradiography (275). The concentration of rat AT 1 and AT 2 receptors at protein level is dependent on the developmental stage.…”
Section: Male Reproductive Tractmentioning
confidence: 92%
See 1 more Smart Citation
“…Aguilera et al (7) reported also a decrease in ANG II binding during development and that in immature rat a high proportion of ANG II receptors in the testes are located in nondifferentiated mesenchymal cells of the interstitium. Hypophysectomy led to a marked increase in AT 1 and AT 2 receptor concentration of rat testis with predominant occurrence of AT 1 receptors measured by in vitro autoradiography (275). The concentration of rat AT 1 and AT 2 receptors at protein level is dependent on the developmental stage.…”
Section: Male Reproductive Tractmentioning
confidence: 92%
“…Hirai et al (275) could verify that the AT 1 and AT 2 mRNA gene expression in rat testis is pituitary dependent. After hypophysectomy, the receptor gene expression was significantly increased.…”
Section: Male Reproductive Tractmentioning
confidence: 99%
“…The components of the renin angiotensin system have long been known to be expressed in the mammalian testis (34,35), and their involvement in the development of rat testis has also been documented (36). The AT2 receptor is present, as the major receptor subtype, during the neonatal stage of testicular development and it subsequently shifts to AT1 subtype during puberty (37).…”
Section: Discussionmentioning
confidence: 99%
“…Ang II has been reported to be capable of inhibiting adenylate cyclase activity in rat Leydig cells, reducing basal and gonadotropin-stimulated cAMP and testosterone production [53,54]. On the other hand, it has also been proposed that Ang II may play a role in testicular growth and/or differentiation [55]. Finally, the Ang II receptors AT1R and AT2R have also been detected in rat, monkey and human testes, specifically in Leydig cells [53,56,57].…”
Section: The Renin/ace/ang Ii/at1r/at2r Axismentioning
confidence: 99%